Narratives of Resistance: Mahasweta Devi’s “Draupadi” - Silva, Neluka (SARE: Southeast Asian Review of English, 2018)
This essay explores women’s participation in revolutionary practice, as mapped out in Mahasweta Devi’s short story “Draupadi”. Does Devi romanticise the female revolutionary or centralise the limitations of counter-state activity? This question leads to the way that nationalism, as embodied by the state (through the character of Senanayak), is foregrounded in the text. The restrictions placed upon women by the nation-state are juxtaposed against the issue of female subjectivity, and dominant myths of femininity become a vehicle for mediating notions of female behaviour. I will argue that during nationalist crises, in particular, when the nation is most vulnerable, nationalist signifiers are rigorously applied. Nationalist crises empower Devi’s protagonist, whose suffering enables her to go beyond the boundaries of myth, so that in the short story “Draupadi” the mythical figure is reconstructed (as Dopdi) to produce a counter-narrative by deploying the female body and sexuality as the locus of resistance. In selecting the Draupadi myth as a model for the subaltern woman, Devi calls attention to the politics of myth, of how some myths are privileged (like the Sita myth) while the ambiguities within others (like the Draupadi myth) marginalise women. Devi’s protagonist is situated at the point of breakdown between myth and its “real-life” context and finds that it is through extreme, “terrifying” measures that one can secure agency, even if it is only in fictional narratives.